Enantioselective heterogeneous bronsted acid catalysis - Mutyala, Anil Kumar; Patil, Nitin T. (Organic Chemistry Frontiers, 2014)
This highlight describes the synthesis and catalytic activities of heterogeneous chiral Bronsted acid catalysts. The heterogeneous catalysts are stable, easily separable from the reaction mixture and can be used multiple times without any loss of activity. As a remarkable particularity, the use of heterogeneous catalyst systems has been exemplified for designing continuous flow reactors.